Optimalisasi Perlindungan Ekspresi Budaya Masyarakat Adat di Indonesia - Intan Nevia Cahyana; Ahmad Sabirin (Jurnal Ilmiah Kebijakan Hukum, 2023)
There are approximately 33 types of Indonesian culture that have been claimed as belonging to other countries. Among others, there are Reog Ponorogo and Kuda Lumping Dance; both are from East Java. This proves that the regulation of protection related to TCSe in Indonesia has not provided satisfaction to this nation. Based on this phenomenon, the authors are interested in providing solutions through this research. The type of research is juridical-normative. Furthermore, this research intends to define the TCSe protection mechanisms to assist the Indonesian economy given that legal efforts in developing the "expressions of folklore" will benefit the regional economy. After conducting the research, the authors concluded two major findings. First, so far, the protection of TCSe has not been regulated specifically. As a result, TCSe does not have a strong position concerning its legality. Therefore, it becomes vulnerable and blemishes the occurrence of recognition by othercountries which results in losses to the state economy. Second, specific regulations and anti-theft task forces or advocacy groups are urgently needed to help the indigenous people protect the rights of their distinctive intellectual property. Thus, specialized institutions, which control access and benefit-sharing arrangements with foreign users, are required.